Manajemen Sumber Daya Manusia Dalam Peningkatan Profesionalisme Guru - Arwatin Nurunniyah (THE JOER: Journal Of Education Research, 2023)
Human resource management as a strategic approach to the skills, development motivation and management of organizing human resources to achieve the goals of the institution. A teacher who is said to be professional is a teacher who has special abilities and expertise in the field of teaching. So that teachers are able to carry out their duties and functions as teachers with maximum abilities. Research focus: 1) How is the human resource planning for SDIT Al Adzkia teachers? 2) How is the development of human resources in increasing the professionalism of SDIT Al Adzkia teachers? The purpose of this study is to describe teacher human resource planning and human resource development in increasing teacher professionalism at SDIT Al Adzkia This study uses a descriptive approach and the type is qualitative. Data collection techniques are: (1) Interview (2) Observation and (3) Documentation. While the data analysis with the steps: (1) data collection, (2) data presentation and, (3) drawing conclusions. For the validity of the data using source triangulation. Findings: 1) The principal of SDIT Al Adzkia Jombang plans, implements and evaluates work programs, such as improving the quality of educator resources, making semester programs together with teachers, teacher training activities and implementing teacher delegation in periodic workshops/ training/ guidance activities. At the beginning of each school year, all deputy principals make plans for school activities and budgets, especially the curriculum in which there is a Human Resources Development Program that handles the needs and development of educator resources. 2) Teacher training and development aims to discover and bring out the potential that exists in teachers for the purpose of developing professionalism and strengthening the academic insight of educators, both in terms of competence, managerial, and behavior, so as to make a positive contribution to schools that are continuously in accordance with developments. competition and positions in science, the expectations of the potential and knowledge of teachers are increasing and developing so that they have a positive effect on the progress of the school's qualifications and competencies. A teacher must always upgrade the knowledge they have, because educators are agents of learning and role models for their students.